PENGARUH PROMOSI DAN KUALITAS PELAYANAN JASA GRABFOOD TERHADAP KEPUASAN KONSUMEN DI KELURAHAN BOJA - Bambang Widjanarko Susilo; Elmareza Aizzani; Eni Endaryati; Sri Wahyuning; Haryo Kusumo (MANAJEMEN, 2025)
This study aims to explore the extent to which promotion and service quality affect GrabFood customer satisfaction among Generation Z who live in Boja Village. This study uses a quantitative method with a survey approach, where data is obtained from 100 respondents who are active users of GrabFood through the distribution of questionnaires. To test the proposed hypothesis, multiple linear regression analysis was used. The findings of the study showed that promotion (with a regression coefficient of 0.45) and service quality (regression coefficient of 0.55) both had a positive and significant impact on the level of consumer satisfaction and the Rvalue of 2 was 0.6 that 60% of the consumer satisfaction variable could be explained by the variables of promotion and service quality, The validity of the regression model used was confirmed through a classical assumption test. These results highlight the importance of synergy between the implementation of effective promotional strategies and service quality improvement to create an optimal customer experience. The practical implications of this research can be used by GrabFood management in designing more efficient marketing strategies to increase customer satisfaction and loyalty. In conclusion, the synergy between effective promotional strategies and improving service quality is the key to creating an optimal customer experience and increasing the satisfaction and loyalty of GrabFood users in the region